Room temperature quantum cascade laser with ∼31% wall-plug efficiency - F. Wang (AIP Advances, 2020)
In this article, we report the demonstration of a quantum cascade laser emitting at λ ≈ 4.9 μm with a wall-plug efficiency of ∼31% and an output power of ∼23 W in pulsed operation at room temperature with 50 cascade stages (Ns). With proper fabrication and packaging, this buried ridge quantum cascade laser with a cavity length of 5 mm delivers more than ∼15 W output power, and its wall-plug efficiency exceeds ∼20% at 100 °C. The experimental results of the lasers are well in agreement with the numerical predictions.